2006
DOI: 10.1021/jo062073s
|View full text |Cite
|
Sign up to set email alerts
|

RuCl3-Catalyzed Oxidation of Iodoarenes with Peracetic Acid:  New Facile Preparation of Iodylarenes

Abstract: New facile methodology for the preparation of pentavalent iodine compounds using peracetic acid as an oxidant in the presence of catalytic amounts of ruthenium trichloride is described. The new procedure allows the preparation of several previously unknown iodylarenes bearing strongly electron-withdrawing CF3 groups in the aromatic ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…2 ) the I–O bonds are much longer (≈2.5–2.6 Å). It is known from the literature that the preparation of iodine(V) species from ArI and an oxidant involves initial formation of ArIO followed by disproportionation to ArI and ArIO 2 [ 23 ]. Such disproportionation is significantly impeded or even impossible in the cyclic structure of 2-iodosylbenzenesulfonic acid.…”
Section: Resultsmentioning
confidence: 99%
“…2 ) the I–O bonds are much longer (≈2.5–2.6 Å). It is known from the literature that the preparation of iodine(V) species from ArI and an oxidant involves initial formation of ArIO followed by disproportionation to ArI and ArIO 2 [ 23 ]. Such disproportionation is significantly impeded or even impossible in the cyclic structure of 2-iodosylbenzenesulfonic acid.…”
Section: Resultsmentioning
confidence: 99%
“…13 Further studies have demonstrated that the use of Oxone Ò as the oxidant instead of peracetic acid leads to even milder reaction conditions. In a typical procedure, treatment of iodobenzene with Oxone Ò in aqueous acetonitrile at room temperature in the presence of RuCl 3 (0.16 mol %) results in the formation of iodylbenzene (PhIO 2 ) n , which can be isolated from the reaction mixture in a 59% preparative yield (Scheme 2).…”
Section: Transition Metal-mediated Oxidations Utilizing Iodine(v) Spementioning
confidence: 99%
“…23 g, 5.0 mmol) according to the general procedure afforded 0.50 g (36%) of product, isolated as microcrystalline solid, mp 173e175 C. 1 H NMR (DMSO-d 6 ): d 7.94 (d,J¼7.5 Hz,1H),7.57 (m,3H), 3.22 (septet, 6.5 Hz, 1H), 1.29 (d, 7.0 Hz, 6H). 13 C NMR (DMSO-d 6 ): d 148. 7, 147.0, 132.1, 127.1, 126.9, 122.6, 33.0, 23.7 To a mixture of iodobenzene (0.204 g, 1 mmol) and Oxone Ò (0.33 g, 0.54 mmol) in 3 mL of aqueous acetonitrile (MeCN/H 2 O, 1:1) an aqueous solution of RuCl 3 (10 mL of standard 0.16 M solution; 0.…”
Section: 2mentioning
confidence: 99%
“…O mesmo grupo utilizou estratégia análoga em outras aplicações, 21 incluindo a preparação e aplicação de iodilarenos. [22][23][24] A desproporção de compostos de I(III) também foi investigada por Kita e colaboradores que, após realizarem a oxidação de alcoóis utilizando PhIO/KBr em água, 25 fizeram um estudo sobre o mecanismo da reação para averiguar o envolvimento de espécies de I(V), o que não se confirmou. 26 Apesar da importância da desproporção de reagentes de I(III), pouco se tem feito para entender o mecanismo desta reação.…”
Section: Introductionunclassified